(untitled) (International Journal of Health, Animal Science and Food Safety, 2015)
Large quantities of serum are produced during the strained yoghurt manufacturing process, which is the predominant type of yoghurt in Greece. However, the exploitation of this by-product as an alternative source of energy, protein and mineral elements in animal diets has not yet been examined. Therefore, this experiment was conducted to determine the effects of dietary yoghurt serum supplementation on growth performance and antioxidant status in sheep. Fourty eight male 2 months old lambs of Chios breed were randomly assigned to three experimental groups; control group was fed with a commercial basal diet, whereas the other two groups consumed the same diet, with the only difference that concentrated feed was uniformly supplemented with two levels of yoghurt serum powder (YS1: 25 g/kg feed or YS2: 50 g/kg feed). Lambs were weighed in a weekly basis from the beginning until the end of the experiment and blood samples were collected to measure antioxidant status. No significant effect of yoghurt serum powder on growth performance of fattening lambs was demonstrated, even after 28 days of dietary supplementation (P>0.05). At the same time, malondialdehyde (MDA) levels in blood plasma were not significantly different among the experimental groups (P>0.05) and no incidents of lambs with diarrhea were recorded. It can be concluded that yoghurt serum powder appears as a promising alternative of the cereals in the diets of fattening lambs, since no negative effects on growth performance and health status were observed.